Shear performance of headless studs in ultra-high performance concrete bridge deck - Jiang, Haoting; Wang, Hongjie; Deng, Xilei; Li, Yongguang; Zhou, Heying; Wu, Chaolan; Jiang, Jinlong (Frontiers in Materials, 2024)
Conventional stud connectors were proved to be inconvenient for the later disassembly and replacement in ultra-high performance concrete (UHPC) bridge decks. In this study, the headless studs which is a type of studs with their heads removed were employed as a substitute for conventional stud connectors, aiming to enhance the detachability of the bridge decks on the premise of ensuring the anti-lift bearing capacity of the decks. Three push-out specimens containing the headless studs with a diameter of 13 mm were carried out to study the mechanical properties of headless studs. In addition, the finite element model was developed to reveal the failure mechanism of headless studs in UHPC.Results indicated that the load-slip curve of headless stud connector can be divided into elastic stage, plastic stage and failure stage. The failure mode of headless studs was the shear fracture at the root of stud shank. Headless stud connections under cyclic loading can produce greater plastic deformation.The ultimate shear capacity and shear stiffness of headless studs were lower than those of conventional studs. Additionally, the UHPC slabs configured with headless studs have a small quantity of separation at the steel-UHPC interface, so it is suggested to use headless studs and conventional studs together in UHPC slabs to ensure the necessary anti-lift bearing capacity. Finite element analysis indicated that in the elastic stage, the bearing capacity of the push-specimen was dominated by the material properties of the headless stud. After entering the plastic stage, the bearing capacity of the push-specimen was mainly controlled by the UHPC below the headless stud.